2018
DOI: 10.31512/ricsb.v2i2.2548
|View full text |Cite
|
Sign up to set email alerts
|

Biofilmes em infecção por Candida: uma revisão da literatura

Abstract: <p><strong>Objetivo: </strong>Realizar uma revisão narrativa apresentando alguns resultados de pesquisas sobre a formação de biofilmes por espécies do gênero <em>Candida</em>.<strong> Materiais e Métodos:</strong> As etapas de realização desta revisão narrativa foram: definição da questão norteadora; seleção dos artigos para o estudo; elaboração do quadro sinóptico com as principais informações de cada artigo; análise dos achados de acordo com os critérios estabelecido… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
1
0
1
Order By: Relevance
“…Sorbitol serves as an osmotic protector and can be used to assess whether a molecule acts on the fungal cell wall or not [ 56 ]. Thus, the absence of changes in the MIC of the tested compound, in the presence of sorbitol in the culture medium, indicates that its action is not related to the fungal cell wall [ 57 , 58 , 59 ]. In this study, it is observed that (E)-benzylidene-chroman-4-one does not have a mechanism of action defined by interference with structures involved in the functions of the cell wall, although the in silico test predicted an affinity of the compound with the enzyme 1,3β-glucan synthase.…”
Section: Discussionmentioning
confidence: 99%
“…Sorbitol serves as an osmotic protector and can be used to assess whether a molecule acts on the fungal cell wall or not [ 56 ]. Thus, the absence of changes in the MIC of the tested compound, in the presence of sorbitol in the culture medium, indicates that its action is not related to the fungal cell wall [ 57 , 58 , 59 ]. In this study, it is observed that (E)-benzylidene-chroman-4-one does not have a mechanism of action defined by interference with structures involved in the functions of the cell wall, although the in silico test predicted an affinity of the compound with the enzyme 1,3β-glucan synthase.…”
Section: Discussionmentioning
confidence: 99%
“…A transição morfológica das células leveduriformes e hifas formam o biofilme, que é considerado a característica de virulência mais relevante da espécie C. albicans, a qual demonstram a resistência aos antifúngicos. Onde as células se multiplicam, há a agregação de novas células, produção e aumento de hifas e da densidade do biofilme, além da produção de moléculas auto indutoras, indução da transcrição genes específicos reguladores da virulência, motilidade, e da produção da matriz polimérica extracelular (EPS), conferindo maior resistência ao ataque de agentes antimicrobianos e desinfetantes, radiação ultra-violeta e desidratação (Langer et al, 2018).…”
Section: Fatores De Virulênciaunclassified